EFFECTS OF AMLODIPINE ON SERUM TESTOSTERONE, TESTICULAR WEIGHT AND GONADO-SOMATIC INDEX IN ADULT RATS - Latif, Rabia; Lodhi, Ghulam Mustafa; Aslam, Muhammad (Journal of Ayub Medical College Abbottabad, 2008)
Background: Calcium ions are vital in many biological processes including hormonal secretion, mitosis, reproduction, fertility and regulation of gene expression. Thus, calcium antagonists who are frequently prescribed for the cure of cardiovascular diseases may affect any of these physiological processes. Methods: This quasi experimental study was done at Army Medical College, Rawalpindi from October 2007 to March 2008. Thirty male Sprague Dawley rats, purchased from National Institute of Health, Islamabad were divided into group A (vehicle treated controls) and group B (amlodipine treated). After receiving drug treatment for 50 days, all the rats were sacrificed. Serum was stored to measure testosterone by enzyme immunoassay technique. The testes were removed for measuring absolute testicular weight and gonado-somatic index. Results: Serum testosterone, absolute testicular weight and gonado-somatic index were found to be significantly reduced in amlodipine treated rats. Conclusion: These results suggest that long term treatment with amlodipine might be associated with significant testicular regression and reduction in serum testosterone. Furthermore, since dihydopyridine antagonists are widely used in hypertension, our data may have some clinical implication in the management of infertility associated with hypertension. Keywords: adverse effects, calcium channel blocker, amlodipine, testosterone, testis, gonadosomatic index